EASTERN FAMILY EDUCATION IN THE EYES OF OUR COUNTRY! - D. Abdullaeva (Galaxy International Interdisciplinary Research Journal, 2022)
In the article, the reforms in the education system, innovative changes, training of highly qualified specialists for the homeland, family, creating the necessary and sufficient conditions for the participants of the education process in order to improve the quality and efficiency of education, in accordance with the requirements of the labor market, are carried out in the article. is shown to be increasing.